Effect of Aeration Time Variation on Iron (Fe) Level in Well Water: Pengaruh Variasi Lama Waktu Aerasi Terhadap Kadar Besi (Fe) pada Air Sumur - Saputro, Maarif Ardhi; Astuti, Dwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Iron (Fe) levels in wells that exceed quality standards can cause the water to turn yellow, deposition on the pipe walls, bacterial growth, change in the taste of the water, and turbidity. One way to deal with excessive levels of iron (Fe) in water is aeration. This study aims to determine variations in the length of aeration time on iron (Fe) content in well-healthy Sumber Village, Simo District, Boyolali Regency. This research is a post-only design. The population of this study was all healthy in the houses of residents in Simo Village, Simo District, and Boyolali Regency. The sample is resident well water with a characteristic fishy smell, turbidity, and a yellowish color. Sampling with a quota sampling of 240 liters was taken in the morning before residents used the well. Statistical analysis using the ANOVA test yielded p0.000 <p0.05, so there was a significant effect between the length of aeration time and the healthy water's iron (Fe) content. Follow-up tests used the Tukey HSD test to determine the most effective time for reducing iron (Fe) levels, with the highest mean difference of 0.40833 in the treatment with 9 minutes of aeration time. The results showed that the most effective aeration time to reduce iron (Fe) content to 0.78 mg/l was 9 minutes. This study concluded that the aeration process c to reduces high levels of iron (Fe) in wells.